'LIKE GENDER, ORGANISED RELIGION IS A COMPLEX MATTER': THE GROWING ACCEPTANCE OF TRANSGENDER PEOPLE IN PROTESTANT CHRISTIANITY. Issue 4 (October 2017) - Dormor, Duncan
Abstract : Over the last couple of decades many liberal and mainstream Protestant denominations have welcomed transgender Christians as congregational members and affirmed their ministry as leaders and teachers. A growing number of Protestant churches in Europe and the USA ordain transgender people as pastors and teachers and conduct weddings for transgender people in their confirmed gender. The issues raised by transgender are complex for religious authorities and churches in the modern world, as they have an impact upon communities, relationships between believers, and shared understandings of the sacred. Three catalysts for change have been: ministers or priests who have transitioned and sought clear validation about their continuing public role as Christian teachers and leaders; the requirement for churches to respond to newly-introduced legislation which gives transgender people certain marriage and employment rights; and the consciousness-raising of a growing number of advocates and lobbying groups within the churches. Consequently, there has been slow but steady progress in the acceptance of transgender people within the Christian community across the spectrum of mainstream Protestant denominations.